Fables of subversion satire and the American novel, 1930 - 1980 - Weisenburger, Steven 1949- (Univ. of Georgia Press, 1995)
Chapters focus on theories of satire, early subversions of satiric conventions by Nathanael West, Flannery O'Connor, and John Hawkes, the flowering of "Black Humor" fictions of the sixties, and the forms of political and encyclopedic satire prominent throughout the period. Many of the writers included here, such as Vladimir Nabokov, William Gaddis, Kurt Vonnegut, Robert Coover, and Thomas Pynchon, are acknowledged masters of contemporary humor. Others, such as Mary McCarthy, Chester Himes, James Purdy, Charles Wright, and Ishmael Reed, have not previously been considered in this context. Posing a seminal challenge to existing theories of satire, Fables of Subversion explores the iconoclastic energies of the new satires as a driving force in late modern and postmodern novel writing